TLR4 genetic variation is associated with inflammatory responses in Gram-positive sepsis. (January 2017) - Chantratita, N.; Tandhavanant, S.; Seal, S.; Wikraiphat, C.; Wongsuvan, G.; Ariyaprasert, P.; Suntornsut, P.; Teerawattanasook, N.; Jutrakul, Y.; Srisurat, N.; Chaimanee, P.; Mahavanakul, W.; et al.
Abstract: Objectives: To identify important pathogen recognition receptor (PRR) pathways regulating innate immune responses and outcome in Staphylococcus aureus sepsis. Methods: We analysed whether candidate PRR pathway genetic variants were associated with killed S. aureus –induced cytokine responses ex vivo and performed follow-up in vitro studies. We tested the association of our top-ranked variant with cytokine responses and clinical outcomes in a prospective multicentre cohort of patients with staphylococcal sepsis. Results: An intronic TLR4 polymorphism and expression quantitative trait locus, rs1927907, was highly associated with cytokine release induced by stimulation of blood from healthy Thai subjects with S. aureus ex vivo . S. aureus did not induce TLR4-dependent NF-κB activation in transfected HEK293 cells. In monocytes, tumor necrosis factor (TNF)-α release induced by S. aureus was not blunted by a TLR4/MD-2 neutralizing antibody, but in a monocyte cell line, TNF-α was reduced by knockdown of TLR4. In Thai patients with staphylococcal sepsis, rs1927907 was associated with higher interleukin (IL)-6 and IL-8 levels as well as with respiratory failure. S. aureus –induced responses in blood were most highly correlated with responses to Gram-negative stimulants whole blood. Conclusions: A genetic variant in TLR4 is associated with cytokine responses to S. aureus ex vivo and plasma cytokine levels and respiratory failure in staphylococcal sepsis. While S. aureus does not express lipopolysaccharide or activate TLR4 directly, the innate immune response to S. aureus does appear to be modulated by TLR4 and shares significant commonality with that induced by Gram-negative pathogens and lipopolysaccharide.